Spatial Ability of Grade VIII Students in Terms of Van Hiele's Level of Thinking - Sabila Mukhlishonisa; Al Jupri; Jarnawi Afgani Dahlan (PRISMA, 2026)
Spatial ability is important in learning geometry, especially related to 3D shapes. This study aims to analyze students' spatial ability based on van Hiele's geometry thinking level. The research was conducted with a qualitative case study approach involving 23 students of grade VIII at one of the public junior high schools in Bandung, West Java. The researchers gave two types of tests to students, namely spatial tests based on spatial perception, visualization, mental rotation, spatial relation, and spatial orientation elements, as well as geometry thinking tests based on van Hiele's five levels of thinking, namely visualization, analysis, informal deduction, deduction, and rigor. The results show that about half of students reached the visualization level with low spatial orientation ability, while the rest of students have not reached the visualization level with very low spatial orientation ability. The spatial ability of students in the spatial perception element is categorized as high, in the visualization and spatial relation elements is categorized as sufficient, and in the mental rotation element is categorized as low. Students' ability to see objects from various directions and to rotate objects still needs to be improved.